Concrete-steel composite action performance in steel girder bridges under earthquake loading - Adnan, Azlan; Mohd. Ghazali, Mohd. Zulkifli (1999)
Steel girder bridges are commonly built in the U.S.A and currently widely adopted to Malaysia. The study includes the performance of the studs when subject to earthquake in different directions and intensity of earthquake motions by performing the finite element modeling of the overall structures. The linear structural analysis under the earthquake loading shows that the stud has to carry more internal forces in shear and axial directions. These occurrences suggest better precaution have to be taken on the design of the stud for bridges in the earthquake prone regions include regions in the low intensity earthquake level